Accuracy of integrated total pelvic floor ultrasound compared to defaecatory MRI in females with pelvic floor defaecatory dysfunction - Hainsworth, Alison J (Br J Radiol, 2016)
OBJECTIVE: Defaecatory MRI allows multicompartmental assessment of defaecatory dysfunction but is often inaccessible. Integrated total pelvic floor ultrasound (transperineal, transvaginal, endoanal) may provide a cheap, portable alternative. The accuracy of total pelvic floor ultrasound for anatomical abnormalities when compared with defaecatory MRI was assessed. METHODS: The dynamic images from 68 females who had undergone integrated total pelvic floor ultrasound and defaecatory MRI between 2009 and 2015 were blindly reviewed. The following were recorded: rectocoele, enterocoele, intussusception and cystocoele. RESULTS: There were 26 rectocoeles on MRI (49 rectocoeles on ultrasound), 24 rectocoeles with intussusception on MRI (19 rectocoeles on ultrasound), 23 enterocoeles on MRI (24 enterocoeles on ultrasound) and 49 cystocoeles on MRI (35 cystocoeles on ultrasound). Sensitivity and specificity of total pelvic floor ultrasound were 81% and 33% for rectocoele, 60% and 91% for intussusception, 65% and 80% for enterocoele and 65% and 84% for cystocoele when compared with defaecatory MRI. This gave a negative-predictive value and positive-predictive value of 74% and 43% for rectocoele, 80% and 79% for intussusception, 82% and 63% for enterocoele and 48% and 91% for cystocoele. CONCLUSION: Integrated total pelvic floor ultrasound may serve as a screening tool for pelvic floor defaecatory dysfunction; when normal, defaecatory MRI can be avoided, as rectocoele, intussusception and enterocoele are unlikely to be present. ADVANCES IN KNOWLEDGE: This is the first study to compare integrated total pelvic floor ultrasound with defaecatory MRI. The results support the use of integrated total pelvic floor ultrasound as a screening tool for defaecatory dysfunction.